ＩＬ－７タンパク質とＶＥＧＦアンタゴニストの併用による腫瘍の治療方法 (2025)
本開示は、ＩＬ－７タンパク質とＶＥＧＦアンタゴニストとの組み合わせによってがん（または腫瘍）を治療する方法に関する。いくつかの態様では、本明細書に提供される方法は、さらなる治療薬（例えば、免疫チェックポイント阻害剤）を対象に投与することをさらに含む。【選択図】なし The present disclosure relates to methods of treating a cancer (or a tumor) with an IL-7 protein in combination with a VEGF antagonist. In some aspects, the methods provided herein further comprise administering an additional therapeutic agent (e.g., immune checkpoint inhibitor) to the subject.